FRI0446 Severe Heart Disease in Systemic Sclerosis: Prevalence, Risk Factors and Current Treatment. A Eustar-Desscipher Study. (9th June 2015) - Vettori, S.; Cuomo, G.; Jaeger, V.K.; Frerix, M.; Siegert, E.; Lorand, V.; Jordan, S.; Riemekasten, G.; Allanore, Y.; Czirjak, L.; Tarner, I.H.; Distler, O.; et al.
Abstract : Background: Heart disease in patients with systemic sclerosis (SSc) can cause manifestations such as cardiac blocks (CBs), ventricular arrhythmias (VA), and congestive heart failure (CHF) which may require a pacemaker/defibrillator implant, are the cause of death or sudden death (SD) in about 20% of patients and can be referred to as severe heart disease (SHD). The European League against Rheumatism – Scleroderma Trial and Research (EUSTAR) database provides an unique opportunity to address this topic. The results of such analysis are instrumental for the DeSScipher project, an EU funded project devoted to decipher the optimal management of SSc . Objectives: To investigate the prevalence of each SHD manifestation and their associations with demographic, serological, clinical and therapeutic aspects in a large series of adult SSc patients. Methods: Seven EUSTAR-DeSScipher centers provided clinical charts at study entry including all the items of SHD. The prevalence of any and each SHD manifestation was calculated. The associations with demographic, serological, clinical features and treatment with vasodilators, i.e. calcium channel blockers (CCBs) and /or ACE inhibitors (ACEi), were investigated by univariate analysis and confirmed by multivariate logistic regression analysis. Results: At July 6th 2012, 1119 SSc patients from the 7 EUSTAR centers had no missing data (995 females, 164 males; median age 53.6 years, range 14-86). Out of them, 211 patients (19%) had at least 1 SHD manifestation, 152 patients had CBs (14%), 71 had VA (6%), 132 had CHF (12%), and 27 received a pacemaker/defibrillator implant (2%). CBs were the only SHD manifestation in 100 patients, VA in 31, and CHF in 80. No association was found between SHD and clinical (diffuse or limited) and serological (ACA or anti-Scl-70) subset. No association was found between either CHF or pacemaker/defibrillator implant and any other disease feature. In multiple logistic regression analysis, CBs were associated with bibasilar lung fibrosis at chest X-Ray (OR=2.6; 95%CI=1-6.4; p=0.04), while VA were associated with increased CPK levels (OR=11; 95%CI=1-117; p=0.02) and, unexpectedly, current CCB use (OR 10; 95%CI 1.4-76.1; p=0.02). Conclusions: This is the first study devoted to investigate SHD in a large series of carefully assessed SSc patients. SHD was detected in about 19% of the cases, CBs in 14%, VA in 6%, CHF in 12%. Pacemaker/defibrillator implant was needed in 2.4%. These data highlight the importance of an accurate heart assessment in SSc patients. Moreover, the associations between VA and CPK elevation and current CCB use should stimulate the clinician to avoid these drugs in patients with myositis/myocarditis. Acknowledgements: The DeSScipher project was funded by the European Community's Framework Programme 7 (FP7-HEALTH-2012.2.4.4-2 - Observational trials in rare diseases) under grant agreement N° 305495 Disclosure of Interest: S. Vettori Grant/research support from: Roche, Consultant for: Phadia Thermofisher, Pfizer, Abbvie, G. Cuomo: None declared, V. Jaeger: None declared, M. Frerix: None declared, E. Siegert: None declared, V. Lorand: None declared, S. Jordan: None declared, G. Riemekasten: None declared, Y. Allanore: None declared, L. Czirjak: None declared, I. Tarner: None declared, O. Distler Grant/research support from: 4D Science, Actelion, Active Biotec, Bayer-Schering, Biogen, Biovitrium, BMS, Boehringer Ingelheim Pharma, EpiPharm, Ergonex, GSK, Inventiva, Medac, Novartis, Pfizer, Pharmacyclics, Roche/Genentech, Sanofi/Genzyme, Serodapharm, Sinoxa and United BioSource Corporation, Consultant for: 4D Science, Actelion, Active Biotec, Bayer-Schering, Biogen, Biovitrium, BMS, Boehringer Ingelheim Pharma, EpiPharm, Ergonex, GSK, Inventiva, Medac, Novartis, Pfizer, Pharmacyclics, Roche/Genentech, Sanofi/Genzyme, Serodapharm, Sinoxa and United BioSource Corporation, C. Denton: None declared, M. Matucci-Cerinic: None declared, F. Del Galdo: None declared, U. Walker: None declared, U. Mueller-Ladner: None declared, G. Valentini: None declared